The Keeyask hydro dam plan in northern Canada: a model for inclusive indigenous development?. Issue 1 (2nd January 2017) - Buckland, Jerry; O'Gorman, Melanie
ABSTRACT: This study uses content analysis of an environmental hearing to examine different views on the construction of a hydro dam in northern Manitoba. We found both support for and opposition to the Keeyask dam project, a partnership between the hydro utility and four First Nations communities. Proponents noted the project's inclusive model and employment and revenue benefits for local people. Opponents warned of negative impacts on the environment and psycho-social health, and the risks of working with a utility that has a bad track record. While Keeyask is an improvement over past projects, the partnership will require vigilant monitoring and implementation-to-plan if the benefits are to flow to indigenous people.